Central African Economic and Monetary Community (CEMAC) : Common Policies of Member Countries-Press Release; Staff Report; and Statement by the Executive Director. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses the common policies needed for the member countries of the Central African Economic and Monetary Community (CEMAC). CEMAC growth was subdued in 2015. It slowed to 1.6 percent, from 4.9 percent in 2014, because of reduced public investment and lower oil production. Policies to counter the oil-price shock need to focus on fiscal consolidation and real-economy reforms. In the wake of the oil-price shock, monetary financing has been the primary response tool. Fiscal policy coordination among members should be strengthened, and fiscal discipline enforcement is needed. Real-economy reforms, focusing on improving the business climate and boosting private investment, are also needed to preserve macroeconomic stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet